Honeycomb-like NiCo2S4 nanosheets prepared by rapid electrodeposition as a counter electrode for dye-sensitized solar cells. (24th July 2017) - Yin, Jie; Wang, Yuqiao; Meng, Wenfei; Zhou, Tianyue; Li, Baosong; Wei, Tao; Sun, Yueming
Abstract: Honeycomb-like nickel cobalt sulfide (NiCo2 S4 ) nanosheets were directly deposited on fluorine-doped tin oxide substrate by a rapid voltammetric deposition method. The method was also controllable and feasible for preparing NiCo2 S4 on flexible Ti foil without any heating processes. Compared with Pt, CoS and NiS, NiCo2 S4 exhibited low charge-transfer resistances and excellent electrocatalytic activity for I 3 − reduction, acting as a counter electrode for a dye-sensitized solar cell. The NiCo2 S4 -based solar cell showed higher power conversion efficiency (7.44%) than that of Pt-based solar cell (7.09%) under simulated illumination (AM 1.5 G, 100 mW cm −2 ). The device based on the flexible NiCo2 S4 /Ti foil achieved a power conversion efficiency of 5.28% under the above illumination conditions. This work can be extended to flexible and wearable technologies due to its facile technique.